THE PRESENCE OF AN ORBITOANTORBITAL FENESTRA: FURTHER EVIDENCE OF THE ANUROGNATHID PECULIARITY WITHIN THE PTEROSAURIA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2022)
The anurognathids are peculiar pterosaurs characterized by broad skulls with very short rostra and broadly arched jaws. The presence of distinct or confluent external naris and antorbital fenestra in these pterosaurs has been debated in the last years. The relatively well-preserved specimens of Batrachognathus volans show that the antorbital fenestra was confluent with the orbit forming an enormous orbitoantorbital fenestra. This feature is evident also in Jeholopterus ningchengensis. The consequent modification of the matrices of two recently published phylogenetic analyses about the in-group pterosaur relationships shows that the Anurognathidae are a derived clade of non-monofenestratan pterosaurs. Anurognathidae (including also 'Dimorphodon' weintraubi according to the definition by Hone 2020) are still a scarcely known clade because only a few specimens have been adequately described in the literature.
Keywords: Reptilia; Flying reptiles; Anurognathidae; Batrachognathus volans; Skull; Anatomy.